2022
DOI: 10.3390/polym14193943
|View full text |Cite
|
Sign up to set email alerts
|

Novel Wet Electrospinning Inside a Reactive Pre-Ceramic Gel to Yield Advanced Nanofiber-Reinforced Geopolymer Composites

Abstract: Electrospinning is a versatile approach to generate nanofibers in situ. Yet, recently, wet electrospinning has been introduced as a more efficient way to deposit isolated fibers inside bulk materials. In wet electrospinning, a liquid bath is adopted, instead of a solid collector, for fiber collection. However, despite several studies focused on wet electrospinning to yield polymer composites, few studies have investigated wet electrospinning to yield ceramic composites. In this paper, we propose a novel in-sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Copyright 2022 Multidisciplinary Digital Publishing Institute. (B) Reprinted with permission from ( Xu et al, 2022 ). Copyright 2022 Multidisciplinary Digital Publishing Institute.…”
Section: Hybrid Nanofibers Fabrication Techniquesmentioning
confidence: 99%
“…Copyright 2022 Multidisciplinary Digital Publishing Institute. (B) Reprinted with permission from ( Xu et al, 2022 ). Copyright 2022 Multidisciplinary Digital Publishing Institute.…”
Section: Hybrid Nanofibers Fabrication Techniquesmentioning
confidence: 99%
“…Electrospinning is an easy and inexpensive technique to manufacture ceramic-reinforced polymeric nano ber composites using a high-voltage electric eld. The surface interaction between the polymer and the ceramics reinforced with nano bers produced by electrospinning and the synergy between materials can be examined in many ways [19], [20]. Many researchers have used recent chemistry techniques to uncover the complex mechanism of interactions at the ceramic-polymer interface and how PAN polymer chains interface with the ceramic components of y ash.…”
Section: Introductionmentioning
confidence: 99%
“…Through histological evaluation and immunostaining analysis in rat implants, they demonstrated that the artificial neural catheter promoted nerve axon extension and nerve fiber formation. Furthermore, Xu et al [ 17 ] employed wet electro-spinning technology to produce nano-reinforced ceramic composite fibers in situ. These fibers retained the amorphous structure of the material, increased porosity, and improved fracture toughness, resulting in significant hardening and toughening effects on polymer composites.…”
Section: Introductionmentioning
confidence: 99%